Pengaruh Penggunaan Media Gambar Berseri dalam Peningkatan Keterampilan Menulis Teks Biografi (Penelitian Quasi Eksperimen) pada Siswa Kelas X di SMK Negeri 1 Rawamerta - Asira, Yesi; Huri, Daman; Suprihatin, Dewi (Peneliti.net, 2024)
This thesis research is about the use of serial image media in improving biographical text writing skills for class X students at SMK Negeri 1 Rawamerta. The aim of this research is to determine the use of serial image media in learning so that it can improve the skills of class X students at SMK Negeri 1 Rawamerta in writing biographical texts. The research method used is a quantitative method with a quasi-experimental research type and the research design used is nonequivalent. The aim is to compare the learning outcomes of the two classes used as research samples, namely MPLB 1 class as the experimental class and TO 1 as the control class. In this research, there is an initial test (pretest) to determine students' initial abilities and a final test (posttest) to determine student learning outcomes after being given treatment. The treatment took the form of serial image media for the experimental class, while the control class had conventional learning. The results of research carried out with the help of the SPSS version 26 for Windows program show that the experimental class and control class have different learning outcomes. It is known that the average pretest result for the experimental class is 42.53 and the control class is 36.64, so that the average posttest result for the experimental class is 82.31 while the control class is 61.58. Based on the post-test average, this means that the experimental class is superior to the control class, and there is a significant increase in learning outcomes in the experimental class. Based on the results above, writing skills using serial image media can improve compared to learning before using image media or conventional learning.